PENGEMBANGAN FLASH CARD UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN DENGAN METODE SAS (STRUKTURAL ANALITIK SINTESIS) SISWA SD KELAS I - Budiarti, Wahyu Nuning (Jurnal Tawadhu, 2018)
This study aims to produce a learning media product in the form of Flash Card to improve the initial reading skill with SAS method of first grade students. This development research uses a step developed by Borg & Gall. The development model is grouped into: (1) conducting preliminary research and gathering information, (2) planning, (3) developing the initial product, (4) conducting initial field trials, (5) revising the initial product to compose the main product, (6) conducting major tests, (7) revising the main product to compose the operational product, (8) conducting operational field tests, (9) revising the final product, (10) desemination. The subjects of field test in the experimental class were 27 students and the control class were 27 students. The results showed that (1) Flash Card media suitable for learning. According to material experts and Flash Card product learning experts categorized "good". (2) there is an increase of pretest value on posttest of Indonesian learning motivation and reading comprehension skill between control class and experiment class. Overall test and research results show that the Flash Card media positively and significantly influence to the improvement of reading skill of beginning of SAS method of student.